The Influence of Instagram @Xlaxiata_Iot Social Media Content Messages on Public Knowledge Regarding Ai/Iot (Case Study Xl Axiata – X Camp) - Jiddan Arsyad Lubis (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aims to determine the influence and magnitude of Instagram Social Media Content Messages @xlaxiata_iot influence Public Knowledge regarding AI/IoT (XL Axiata Case Study – X Camp). This research was carried out on Instagram social media @xlaxiata_iot. The research method used is quantitative and simple regression analysis. The population and sample for this research are 100 followers of Instagram social media @xlaxiata_iot. This research shows that the influence of the Instagram Social Media Content Message @xlaxiata_Iot on Community Knowledge related to AI/IoT (XL Axiata Case Study – X Camp) is positive. So, if there is an increase in the factors that determine Instagram media content messages @xlaxiata_Iot, it will directly have an impact on increasing public knowledge. Likewise, if Instagram @xlaxiata_Iot media content messages decrease, then public knowledge will decrease. The magnitude of the influence exerted by the Instagram Social Media Content Message @xlaxiata_Iot on Public Knowledge regarding Ai/Iot (Case Study XL Axiata – 36%. So, it can be concluded that this research shows that there is a contribution of Instagram media content in influencing public knowledge of AI/IoT by 36%. Meanwhile, the remaining 64% is influenced by other factors.